Evaluation of the diagnostic value of circulating tumor cells with CytoSorter® CTC capture system in patients with breast cancer - Lidan Jin; Wenhe Zhao; Jun Zhang; Wenjun Chen; Tan Xie; Linbo Wang; Wanhung Fan; Shuduo Xie; Jianguo Shen; Heming Zheng; Wenxian Hu; Qun Wei; et al. (Cancer Medicine, 2020)
Abstract Purpose In this study, we aimed to investigate the viability of utilizing CytoSorter® system to detect circulating tumor cells (CTCs) and to evaluate the diagnostic value of CTCs in breast cancer (BC). Methods A total of 366 females patients suspected of having BC and 30 healthy female volunteers were enrolled in this study. CTCs were enriched by CytoSorter®, a microfluidic‐based CTCs capturing platform. CTC detection was performed before operation or biopsy. Based on the biopsy results, patients were divided into two groups, namely patients with BC and patients with benign breast diseases (BBD). Patients with BBD and healthy volunteers were serving as controls. The correlation between CTC enumeration and patients' clinicopathological characteristics was evaluated. The receiver operating characteristic (ROC) curve was plotted to assess the diagnostic potency of CytoSorter® system in BC. Results Based on the biopsy results, 130 BC patients at different cancer stages and 236 patients with BBD were enrolled in the study. Seven subjects were dropped out from the study. CTCs were detected in 109 of 128 BC patients, in one of 29 healthy volunteers, and in 37 of 232 patients with BBD. Maximum CTC counts detected in BC patients, healthy volunteers, and patients with BBD were 8, 1, and 4, respectively. Statistical analysis showed CTCs could be used to distinguish BC patients from healthy volunteers and patients with BBD (P < .0001). Circulating tumor cells were statistically associated with patients' cancer stage (P = .0126), tumor size (tumor node metastasis [TNM] T stage, P = .0253), cancer type (invasive vs noninvasive, P = .0141), and lymph node metastasis (P = .0436). More CTCs were found in patients at advanced cancer stage or TNM T stage and in patients with invasive tumor or lymph node metastasis. Furthermore, CTC detection rates in BC patients at Tis and T1‐4 stages were 50%, 81.67%, 91.07%, 100%, and 100%, respectively. When the CTC cut‐off value was set to 2, the ROC curve gave an area under the curve (AUC) of 0.86 with a specificity and sensitivity of 95.4% and 76.56%, respectively. Taken together, CTCs could be used as a diagnostic aid in assistance of cancer screening and staging. Conclusion Circulating tumor cells were successfully isolated in BC patients using CytoSorter® system. CTCs can be used to differentiate BC patients from the patients with BBD or healthy volunteers, and as a diagnostic aid for early cancer diagnosis and cancer staging.